If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -4) + 5(x + 3) = 2(3x + -5) + -6 Reorder the terms: 3(-4 + x) + 5(x + 3) = 2(3x + -5) + -6 (-4 * 3 + x * 3) + 5(x + 3) = 2(3x + -5) + -6 (-12 + 3x) + 5(x + 3) = 2(3x + -5) + -6 Reorder the terms: -12 + 3x + 5(3 + x) = 2(3x + -5) + -6 -12 + 3x + (3 * 5 + x * 5) = 2(3x + -5) + -6 -12 + 3x + (15 + 5x) = 2(3x + -5) + -6 Reorder the terms: -12 + 15 + 3x + 5x = 2(3x + -5) + -6 Combine like terms: -12 + 15 = 3 3 + 3x + 5x = 2(3x + -5) + -6 Combine like terms: 3x + 5x = 8x 3 + 8x = 2(3x + -5) + -6 Reorder the terms: 3 + 8x = 2(-5 + 3x) + -6 3 + 8x = (-5 * 2 + 3x * 2) + -6 3 + 8x = (-10 + 6x) + -6 Reorder the terms: 3 + 8x = -10 + -6 + 6x Combine like terms: -10 + -6 = -16 3 + 8x = -16 + 6x Solving 3 + 8x = -16 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 3 + 8x + -6x = -16 + 6x + -6x Combine like terms: 8x + -6x = 2x 3 + 2x = -16 + 6x + -6x Combine like terms: 6x + -6x = 0 3 + 2x = -16 + 0 3 + 2x = -16 Add '-3' to each side of the equation. 3 + -3 + 2x = -16 + -3 Combine like terms: 3 + -3 = 0 0 + 2x = -16 + -3 2x = -16 + -3 Combine like terms: -16 + -3 = -19 2x = -19 Divide each side by '2'. x = -9.5 Simplifying x = -9.5
| 6(2x-5)=42 | | -4x+2(4-3x)=8-10x | | 9x-21=3+3 | | 3r+12=r+34 | | 4p+8=10p+2 | | -x^2+50x-350=0 | | 8t^2-6t=9 | | x^5-x^4+9x^3-9x^2=0 | | 2x+3=24 | | 5x^2+36x+36=0 | | 6(x-8)-(2x-2)=5x-1 | | .5(20z+18)-8=9(z-3) | | 7x+19y=-3 | | -4c+1=-7 | | 12n-6=4n+10 | | 3(y+-4)+9(y+1)= | | 11m^2-2m=10 | | 4(3+c)=3(c-4) | | 8n-6=10 | | 3t+15=13t | | 7(a+3)=4a | | 10m(4m-9)=30 | | y^2+8y=4 | | 8(w-6)=2w | | 2x-45=43-2 | | 6*(3x-7)-12-4x=9x-(7x+6) | | x-7-7x=5 | | 10u-20=9u-11 | | 3(a+2)=a+12 | | 8s^2-30s+18= | | 16m^2-1=15m | | 2x^2-25x+36=0 |